2010
DOI: 10.1002/ceat.200900547
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flow Pulsation on Forced Convection in a Channel Containing Regularly Spaced Nonconducting Fins

Abstract: The effects of pulsating flow on forced convection in a rectangular channel containing a series of regularly spaced, nonconducting inserts were investigated experimentally. Based on the experimental data, a correlation equation was developed. The steady-flow Reynolds number Re in the laminar range, Re < 1200, was examined. The Prandtl number of the working fluid Pr = 15 and the oscillation was generated using low-frequency oscillation at f < 50 Hz and amplitude A < 1 mm. The energy dissipation as a result of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In addition, they cause curved shear layers, flow deflection, and impingement against the opposite wall. However, higher streamwise pressure drops are associated with the flow in such a system [1,2,[4][5][6]. The flow over the fins is similar to the geometry of shell and tube heat exchangers and of corrugated channels [7].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, they cause curved shear layers, flow deflection, and impingement against the opposite wall. However, higher streamwise pressure drops are associated with the flow in such a system [1,2,[4][5][6]. The flow over the fins is similar to the geometry of shell and tube heat exchangers and of corrugated channels [7].…”
Section: Introductionmentioning
confidence: 95%
“…In addition, the use of long channels is feasible and system fouling can be reduced due to increased wall shear and eddy formation. Several studies have shown that oscillating flow in tubes or parallel ducts with corrugated or finned walls significantly enhances heat and mass transfer in the laminar flow regime [6,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. This influence has been attributed to substantial fluid mixing resulting from the system configuration.…”
Section: Introductionmentioning
confidence: 99%